Interplay Between Insulin Resistance and Immune Dysregulation in Type 2 Diabetes Mellitus: Implications for Therapeutic Interventions - Berbudi A; Khairani S; Tjahjadi AI (ImmunoTargets and Therapy)
Afiat Berbudi,1– 3 Shafia Khairani,4 Adi Imam Tjahjadi2,3,5 1Department of Biomedical Sciences, Parasitology Division, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 2Research Center for Care and Control of Infectious Diseases (RC3ID), Universitas Padjadjaran, Bandung, Indonesia; 3Universitas Padjadjaran Hospital, Sumedang, Indonesia; 4Department of Biomedical Sciences, Cell Biology Division, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 5Department of Biomedical Sciences, Microbiology Division, Faculty of Medicine, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Afiat Berbudi, Department of Biomedical Sciences, Parasitology Division, Faculty of Medicine, Universitas Padjadjaran, Jl. Raya Bandung Sumedang Km. 21, Bandung, West Java, 45363, Indonesia, Tel +62 82297033616, Email a.berbudi@unpad.ac.idAbstract: Type 2 Diabetes Mellitus (T2DM) is a rapidly growing global health issue characterized by insulin resistance and chronic inflammation. Beyond regulating glucose homeostasis, insulin plays a pivotal role in modulating immune cell function, linking metabolic dysregulation with immune responses. This review examines the intricate relationship between insulin resistance and immune dysfunction in T2DM, focusing on how impaired insulin signaling pathways, particularly PI3K/Akt and MAPK, contribute to immune cell activation, proliferation, and chronic inflammation. Insulin resistance impacts immune cells such as T cells, B cells, macrophages, and neutrophils, leading to an imbalance between pro-inflammatory and anti-inflammatory responses. Elevated pro-inflammatory cytokines (eg, TNF-α, IL-6) and adipokines (eg, leptin, resistin) exacerbate insulin resistance, promoting a vicious cycle of metabolic and immune dysregulation. This interplay contributes to the chronic low-grade inflammation that underlies T2DM pathogenesis, further impairing insulin signaling and glucose metabolism. Restoration of insulin sensitivity is, therefore, a critical step toward correcting immune imbalance in insulin-resistant states like T2DM. Therapeutic approaches that reduce inflammation could also support improvements in insulin sensitivity, addressing both metabolic and immune disturbances simultaneously. The review also explores therapeutic strategies, including insulin therapy, targeting insulin signaling pathways, and lifestyle interventions. Insulin therapy can reduce pro-inflammatory cytokine production and enhance anti-inflammatory responses, although challenges such as potential immune suppression and hyperinsulinemia remain. Targeting key signaling pathways and transcription factors offers promising avenues for modulating immune responses, while lifestyle interventions, such as dietary modifications, physical activity, and weight management, can improve insulin sensitivity and reduce inflammation. By understanding the dual role of insulin in regulating both metabolic and immune functions, this review underscores the importance of addressing immune dysfunction as part of comprehensive T2DM management. Targeting the interconnected pathways of insulin signaling and immune regulation could lead to more effective therapeutic approaches, ultimately improving patient outcomes and reducing disease complications.Keywords: insulin resistance, type 2 diabetes mellitus, immune system dysregulation, inflammation, signal transduction, immunomodulation